Effect of Catheter Ablation and Periprocedural Anticoagulation Regimen on the Clinical Course of Migraine in Atrial Fibrillation Patients With or Without Pre-Existent Migraine. (April 2015) - Mohanty, Sanghamitra; Mohanty, Prasant; Rutledge, J. Neal; Di Biase, Luigi; Yan, Rachel Xue; Trivedi, Chintan; Santangeli, Pasquale; Bai, Rong; Cardinal, Deb; Burkhardt, J. David; Gallinghouse, Joseph G.; Horton, Rodney; et al.
<x xml:space="preserve">Abstract</x> Background— We examined the influence of catheter ablation and periprocedural anticoagulation regimen on trajectory of migraine in atrial fibrillation patients with or without migraine history. Methods and Results— Forty patients with (group 1: 64±8 years; men 78%) and 85 (group 2: 61±10 years; men 73%) without migraine history undergoing atrial fibrillation-ablation were enrolled. Migraine status and quality of life were evaluated using standardized questionnaires. Diffusion magnetic resonance imaging of brain was performed for all at pre and 24 hours post procedure. Catheter ablation was performed with (88, 70%) or without (37, 30%) continuous warfarin treatment. Fifty-four patients (11 and 43 from groups 1 and 2, respectively) had subtherapeutic international normalized ratio on procedure day. At 17±5 months follow-up, from group 1, 25 (63%) reported no migraine, 10 (25%) had <1, and 3 (8%) had 2 to 3 monthly symptoms. Intensity of pain decreased from baseline 7 (Q1–Q3, 4–8) to 2 (0–4) scale points at follow-up (P<0.001) and duration of headache from median 8 (Q1–Q3, 4–15) to 0.5 (Q1–Q3, 0–2) hours (P<0.001). Two patients from group 1 reported increased migraine severity and 2 from group 2 had new-onset migraine. Follow-up diffusion magnetic resonance imaging revealed new infarcts in 9.6% (12/125) patients; of which 11 had subtherapeutic preprocedural international normalized ratio on or off continuous warfarin. Quality of life improved significantly in patients with successful ablation, being more pronounced in group 1. Conclusions— In most patients, migraine symptoms improved substantially after catheter ablation. Interestingly, the only cases of new migraine and aggravation of pre-existent headache had subtherapeutic international normalized ratio during the procedure and new cerebral infarcts.